Design of novel enzyme biocatalysts for industrial bioprocess: Harnessing the power of protein engineering, high throughput screening and synthetic biology. (April 2021) - Madhavan, Aravind; Arun, K.B.; Binod, Parameswaran; Sirohi, Ranjna; Tarafdar, Ayon; Reshmy, R.; Kumar Awasthi, Mukesh; Sindhu, Raveendran
Highlights: Engineering strategies for highly efficient enzyme design. Advancement in high throughput screening strategies. Power of computational tools for the design of superior biocatalysts. Abstract: Biocatalysts have wider applications in various industries. Biocatalysts are generating bigger attention among researchers due to their unique catalytic properties like activity, specificity and stability. However the industrial use of many enzymes is hindered by low catalytic efficiency and stability during industrial processes. Properties of enzymes can be altered by protein engineering. Protein engineers are increasingly study the structure–function characteristics, engineering attributes, design of computational tools for enzyme engineering, and functional screening processes to improve the design and applications of enzymes. The potent and innovative techniques of enzyme engineering deliver outstanding opportunities for tailoring industrially important enzymes for the versatile production of biochemicals. An overview of the current trends in enzyme engineering is explored with important representative examples.